Preparative Purification of Recombinant Proteins: Current Status and Future Trends. (17th December 2013) - Saraswat, Mayank; Musante, Luca; Ravidá, Alessandra; Shortt, Brian; Byrne, Barry; Holthofer, Harry
Abstract : Advances in fermentation technologies have resulted in the production of increased yields of proteins of economic, biopharmaceutical, and medicinal importance. Consequently, there is an absolute requirement for the development of rapid, cost-effective methodologies which facilitate the purification of such products in the absence of contaminants, such as superfluous proteins and endotoxins. Here, we provide a comprehensive overview of a selection of key purification methodologies currently being applied in both academic and industrial settings and discuss how innovative and effective protocols such as aqueous two-phase partitioning, membrane chromatography, and high-performance tangential flow filtration may be applied independently of or in conjunction with more traditional protocols for downstream processing applications.